The Salmonella Effector SteA Contributes to the Control of Membrane Dynamics of Salmonella-Containing Vacuoles - Domingues, Lia (American Society for Microbiology, 2014)
Salmonella enterica serovar Typhimurium is a bacterial pathogen causing gastroenteritis in humans and a typhoid-like systemic disease in mice. S. Typhimurium virulence is related to its capacity to multiply intracellularly within a membrane-bound compartment, the Salmonella-containing vacuole (SCV), and depends on type III secretion systems that deliver bacterial effector proteins into host cells. Here, we analyzed the cellular function of the Salmonella effector SteA. We show that, compared to cells infected by wild-type S. Typhimurium, cells infected by ΔsteA mutant bacteria displayed fewer Salmonella-induced filaments (SIFs), an increased clustering of SCVs, and morphologically abnormal vacuoles containing more than one bacterium. The increased clustering of SCVs and the appearance of vacuoles containing more than one bacterium were suppressed by inhibition of the activity of the microtubule motor dynein or kinesin-1. Clustering and positioning of SCVs are controlled by the effectors SseF and SseG, possibly by helping to maintain a balanced activity of microtubule motors on the bacterial vacuoles. Deletion of steA in S. Typhimurium ΔsseF or ΔsseG mutants revealed that SteA contributes to the characteristic scattered distribution of ΔsseF or ΔsseG mutant SCVs in infected cells. Overall, this shows that SteA participates in the control of SCV membrane dynamics. Moreover, it indicates that SteA is functionally linked to SseF and SseG and suggests that it might contribute directly or indirectly to the regulation of microtubule motors on the bacterial vacuoles.